Development of a Home-Based Holistic Dementia Nursing Intervention Model for Family Caregivers - Widyastuti, Rita Hadi; Sahar, Junaiti; Rekawati, Etty (Nurse Media Journal of Nursing, 2025)
Background: The number of older adults with dementia in Indonesia continues to increase. However, many family caregivers still have limited knowledge and skills, leading to adverse effects on both the older adults and the caregivers themselves. Existing interventions mainly focus on single aspects of care and have not adequately addressed the physical, psychological, social, and spiritual dimensions. Therefore, there is a need for a comprehensive intervention model that holistically meets caregivers’ needs.Purpose: This study aimed to develop a home-based holistic dementia nursing intervention model for family caregivers and identify its key features.Methods: Three approaches were used for model development: (1) literature review, (2) in-depth interviews, and (3) expert validation. Five articles addressing holistic care dimensions and nursing interventions were included in the review. Fifteen participants took part in the in-depth interviews, while expert validation involved three specialists in the geriatric field with specific qualifications. Data were collected between August and September 2022. Analysis was conducted by comparing and synthesizing the findings from the literature review, interviews, and expert validation.Results: The holistic dementia nursing intervention model for family caregivers consisted of four intervention domains: (1) physical, (2) psychological, (3) social, and (4) spiritual. The model also incorporated three key components: (1) communication processes, (2) organizational processes, and (3) belief systems.Conclusion: The home-based holistic dementia nursing intervention model for family caregivers offers a potential conceptual framework to comprehensively address the physical, psychological, social, and spiritual needs of both older adults and their caregivers.